Analisis Desain Institusional dalam Seleksi Pantia Pemilihan Kecamatan Kabupaten Sukoharjo Untuk Pemilu Tahun 2024 - Rico Dwi Setiawan; Ahmad Zaki Fadlur Rohman (Journal of Citizenship, 2023)
AbsratctThis study discusses how institutional design forms in KDP selection in Sukoharjo Regency. The formation of the PPK or Sub-District Election Committee is the KPU's full authority for each regency or city. In this study, the PPK selection process in Sukoharjo Regency will be examined, including how the selection process works and the various indicators that influence the selection results for prospective PPK members, especially in the regulations, namely PKPU No. 8 Year 2022 and KPU Decree No. 476 Year 2022. In analyzing the institutional design in the KDP selection process for Sukoharjo Regency, researchers used Elinor Ostrom's Institutional Analysis and Development theory, which includes theories that depart from Neo-Institutionalism. So that in its analysis, this research will look at the regulations, the bio-physical environment, the attributes of the actor community, the action arena, the action situation, and the results of decisions in the Sukoharjo District PPK selection process. This study uses a qualitative approach to research with interview data collection techniques and documentation. The results showed that the KPU of Sukoharjo Regency in carrying out the PPK selection process was normative or in accordance with the template from the RI KPU, and in determining participants who passed the PPK selection, they still tended to consider the track record or organizational background, which is certainly prone to the phenomenon of "networking of friends," especially the final results, which tend to be closed, which strengthens the fact that the PPK selection process is still not going well.Keywords: institutional design, PPK, institutional analysis, and development AbstrakPenelitian ini membahas tentang bagaimana bentuk desain institusional dalam seleksi PPK di Kabupaten Sukoharjo. Pembentukan PPK atau Panitia Pemilihan Kecamatan sendiri merupakan kewenangan penuh KPU masing-masing kabupaten/kota. Dalam penelitian ini, proses seleksi PPK di Kabupaten Sukoharjo akan dilihat bagaimana proses seleksi tersebut berjalan dan berbagai indikator yang mempengaruhi hasil seleksi calon anggota PPK tersebut terkhusus dalam regulasinya yaitu PKPU No. 8 Tahun 2022 dan SK KPU No. 476 Tahun 2022. Dalam menganalisis desain institusional dalam proses seleksi PPK Kabupaten Sukoharjo ini, peneliti menggunakan teori Institusional Analysis and Development milik Elinor Ostrom, yang mana termasuk teori yang berangkat dari Neo-Institusionalism. Sehingga dalam analisisnya, penelitian ini akan melihat regulasi, lingkungan bio-fisik, atribut komunitas aktor, arena aksi, situasi aksi, hingga hasil keputusan dalam proses seleksi PPK Kabupaten Sukoharjo tersebut. Penelitian ini menggunakan metode penelitian pendekatan kualitatif dengan teknik pengumpulan data wawancara dan dokumentasi. Hasil penelitian menunjukan bahwa KPU Kabupaten Sukoharjo dalam menjalankan proses seleksi PPK bersifat normative atau sesuai template dari KPU RI dan dalam menentukan peserta yang lolos seleksi PPK masih cenderung mempertimbangkan rekam jejak atau latar belakang organisasi yang tentunya rawan terjadinya fenomena networking of friends apalagi hasil akhir yang cenderung tidak terbuka yang memperkuat bahwa proses seleksi PPK masih belum berjalan dengan baik.Kata Kunci: Desain Institusional, Seleksi PPK, Institutional Analysis and Development